Electromagnetic response of 3D-printing carbon-containing matrix structure at Sub-THz frequency range - Badin, Alexander V.; Kuleshov, Grigoriy Е.; Bilinsky, Kirill V.; Simonova, Kseniya V. (2020 21st International conference of young specialists on micro/nanotechnologies and electron devices (EDM 2020), Chemal, Russia, 29 June - 3 July 2020)
In this paper the results of a research in the subTHz range of the electromagnetic response of matrix structures based on a carbon-containing polymer obtained by 3D printing are presented. Frequency dependences of the transmission coefficient, complex permittivities of matrix structures samples at the frequency range 48-258 GHz are shown. A comparative analysis of the electromagnetic characteristics of the matrix structures with a solid material was carried out.